George Heriot Postmaster-Painter of the Canadas - Finley, Gerald (University of Toronto Press, 2019)
George Heriot (1759-1839), a Scot, is best known as a skilled landscape watercolourist and as the contentious deputy postmaster general of British North America from 1800 to 1816. He was also a travel writer (his Travels through the Canadas was published in 1807) and a poet. In this volume, a combination of biography and art history, Gerald Finley presents, for the first time, a rounded picture of Heriot, revealing his motives and ideals while also illuminating the texture of life in Canada during the early years of settlement. In describing Heriot's several roles as artist, administrator, patriot, spy, Finley presents a portrait of an eighteenth-century gentleman whose superficial desires were for an active public life but whose deeper yearnings were for a life of contemplation. As a member of the gentry it was natural that Heriot found his way into public service, for which he was suited both by education and by upbringing. Nevertheless, his public career did not always run smoothly and it ended in frustration and sadness. However, through his writing and especially his art Heriot found welcome relief from the tensions of his public duties. Indeed, Heriot's chief importance lies in his art. Trained as a topographical artist, he was an important exponent of the picturesque landscape. As a mode of vision the Picturesque furnished him with a special way of looking at recording the Canadian scene - to him Canada possessed the qualities of Arcadia. This viewpoint served both as aesthetic consolation and as stimulus to inspiration. This volume serves to recognize Heriot's artistic achievement and to accord him the place he deserves in the history of Canadian art and of the country itself
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mrz 2019)
Keywords: Heriot, George -- 1759-1839; BIOGRAPHY & AUTOBIOGRAPHY / Artists, Architects, Photographers; Artists -- Canada -- Biography; Postmasters -- Canada -- Biography; Biografie